The Use of Benesi-Hildebrand Equation in Molecular Complex Formation of o-Nitrophenol with Some Hydrazine Derivatives through Electronic Spectra - Kumar, A.; Sinha, Sushma; Shrivastava, K.P. (Asian Journal of Chemistry, 2010)
The electronic spectra of the molecular complex formation of o-nitrophenol and some hydrazine derivatives have been recorded, with the help of Shimadzu 160A model (Japan) UV spectrophotometer at room temperature. With the Benesi-Hildebrand equation in original form it has been found that it is difficult ot determine the stability constant KAD and molar extinction coefficient εAD of the possible molecular complexes formed in solution.